Neuroprotective effects of yoga practice: age-, experience-, and frequency-dependent plasticity - Villemure, Chantal; Ceko, Marta; Cotton, Valerie A.; Bushnell, Mary Catherine (Frontiers in Human Neuroscience, 2015)
Yoga combines postures, breathing, and meditation. Despite reported health benefits, yoga’s effects on the brain has received little study. We used magnetic resonance imaging to compare age-related gray matter (GM) decline in yogis and controls. We also examined the effect of increasing yoga experience and weekly practice on GM volume and assessed which aspects of weekly practice contributed most to brain size. Controls displayed the well documented age-related global brain GM decline while yogis did not, suggesting that yoga contributes to protect the brain against age-related decline. Years of yoga experience correlated mostly with GM volume differences in the left hemisphere (insula, frontal operculum and orbitofrontal cortex) suggesting that yoga tunes the brain towards a parasympatically-driven mode and positive states. The number of hours of weekly practice correlated with GM volume in the primary somatosensory cortex/superior parietal lobule (S1/SPL), precuneus/posterior cingulate cortex (PCC), hippocampus, and primary visual cortex (V1). Commonality analyses indicated that the combination of postures and meditation contributed the most to the size of the hippocampus, precuneus/PCC, and S1/SPL while the combination of meditation and breathing exercises contributed the most to V1 volume. Yoga’s potential neuroprotective effects may provide a neural basis for some of its beneficial effects.